The potential role of DNA methylation as preventive treatment target of epileptogenesis - Berger, Toni Christoph; Taubøll, Erik; Heuser, Kjell (Frontiers in Cellular Neuroscience, 2022)
Pharmacological therapy of epilepsy has so far been limited to symptomatic treatment aiming at neuronal targets with the result of an unchanged high proportion of patients lacking seizure control. Dissection of the intricate pathological mechanisms that transform normal brain matter to a focus for epileptic seizures - the process of epileptogenesis - could yield targets for novel treatment strategies preventing the development or progression of epilepsy. While many pathological features of epileptogenesis are disclosed, obvious shortcomings of drug development are now believed to be based on the lack of knowledge on molecular upstream mechanisms such as DNA methylation or gene expression, and also the neglect of the importance of glial cell involvement in the inflammatory processes accompanying epileptogenesis. Promising therapeutic approaches with potentially preventive actions may therefore include the manipulation of upstream mechanisms of brain inflammation, comprising epigenetic regulation like DNA methylation and gene expression of glial targets.